2013
DOI: 10.1103/physrevlett.111.136808
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Conductance and Switching in Percolating Nanoparticle Films

Abstract: We demonstrate switching behavior and quantized conductance at room temperature in percolating films of nanoparticles. Our experiments and complementary simulations show that switching and quantization result from formation of atomic scale wires in gaps between particles. These effects occur only when tunnel gaps are present in the film, close to the percolation threshold.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
116
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(121 citation statements)
references
References 34 publications
5
116
0
Order By: Relevance
“…[27]. There it was shown that the probability of obtaining a quantized system conductance when a quantized local conductance was introduced in a tunneling gap increased dramatically as p approached p c ; in that case we replaced the tunnel gaps with the highest field with quantized conductors but did not iteratively solve for a new system conductance, nor did we change V at all.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…[27]. There it was shown that the probability of obtaining a quantized system conductance when a quantized local conductance was introduced in a tunneling gap increased dramatically as p approached p c ; in that case we replaced the tunnel gaps with the highest field with quantized conductors but did not iteratively solve for a new system conductance, nor did we change V at all.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…We note that in this model the conductance can only increase: These simulations are a deliberate simplification of the experimental situation where decreases in conductance are also observed due to breaking of the atomic scale wires by electromigration [27]. It is intuitively clear that if both creation and breaking of connections is possible there will be random switching of the conductance around some mean value that is determined by the relative probabilities of the two types of events.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations